2022
DOI: 10.3390/en15082740
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Heat Transfer Materials by Potassium-Contaminated Ilmenite Bed Particles in Chemical-Looping Combustion of Biomass

Abstract: This study discusses the potential corrosion of boiler materials in chemical-looping combustion (CLC) of biomass. The CLC of biomass has the potential to negative CO2 emission in heat and power production. Biomass fuels, however, typically contain compounds of alkali metals, especially potassium and chloride, which may lead to the corrosion of heat-transfer surfaces in the reactors. The influence of potassium-contaminated ilmenite bed material deposits on the corrosion of seven heat transfer materials used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A series of corrosion tests with K-doped ilmenite has led to this conclusion. 35 Further, Gogolev et al 36 showed with alkali emission measurements in CLC pilot experiments that fuel alkali is largely retained in the ilmenite. They also observed that gas-phase alkali was released mainly in the fuel reactor.…”
Section: Ash Interactions With Bed Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of corrosion tests with K-doped ilmenite has led to this conclusion. 35 Further, Gogolev et al 36 showed with alkali emission measurements in CLC pilot experiments that fuel alkali is largely retained in the ilmenite. They also observed that gas-phase alkali was released mainly in the fuel reactor.…”
Section: Ash Interactions With Bed Materialsmentioning
confidence: 99%
“…Thus, ilmenite seemed to stabilize the K released from the fuel and hinder it from further interacting with the boiler surfaces. A series of corrosion tests with K‐doped ilmenite has led to this conclusion 35 . Further, Gogolev et al 36 .…”
Section: Introductionmentioning
confidence: 94%
“…Alkali species released to the gas-phase are known to cause fouling and corrosion of heat exchange equipment in contact with the flue gases [ 15,17,18,23,42]. In biomass fluidized bed boilers used for steam production, steam superheaters are operated at temperatures of approximately 400-600 • C, while typical combustion temperatures are maintained in the range of 800-900 • C [15,17].…”
Section: Implications Of Alkali Release and Retentionmentioning
confidence: 99%
“…Ilmenite, an iron-titanium oxide mineral (FeTiO 3 ), has also emerged as a promising OC material due to its attractive properties and is now considered one of the most scrutinized OC materials [48,49]. Ilmenite is a robust and durable OC material that possesses high oxygen-carrying capacity, good chemical stability and low cost, making it a viable alternative to other OC materials [28,[50][51][52].…”
Section: Introductionmentioning
confidence: 99%